The serotonergic system and cognitive function - Švob Štrac Dubravka (De Gruyter, 2016)
Symptoms of cognitive dysfunction like memory loss, poor concentration, impaired learning and executive functions are characteristic features of both schizophrenia and Alzheimer’s disease (AD). The neurobiological mechanisms underlying cognition in healthy subjects and neuropsychiatric patients are not completely understood. Studies have focused on serotonin (5-hydroxytryptamine, 5-HT) as one of the possible cognitionrelated biomarkers. The aim of this review is to provide a summary of the current literature on the role of the serotonergic (5-HTergic) system in cognitive function, particularly in AD and schizophrenia.